Quantitative and qualitative differences according to the shoe type for the grand jete landing in ballet - Yi, K. O.; Park, H. R. (Korean Journal of Sport Biomechanics, 2011)
The purpose of this study was to analyze quantitative and qualitative differences according to shoe type for the grand jete landing in ballet. The subjects for this study were 9 female ballet majors with an average of 12 years of experience. Subjects jumped, performing a front split, and landed on 1 foot, a movement called the grand jete. Analysis was performed on the students` landing. Independent variables were 3 shoe types: split sole, traditional out sole, and 5-toed forefoot shoes, with bare feet as a control group. Dependent variables were vertical passive ground reaction force and qualitative elements. Passive ground reaction force variables(maximum passive peak value, number of passive peaks, passive force-time integral, and center of pressure) were measured by the Kistler 928IB Force Platform. Qualitative elements were comfort, cushioning, pain, and fit. Statistical analysis included both 1-way ANOVA and Tukcy's test for follow-up. Finalized data demonstrated that the 5-toed forefoot shoe allows the forefoot to expand and the toes to individually press down upon landing, increasing foot contact with the surface. Five-toed forefoot shoes minimize passive peaks and pain, while increasing comfort, cushioning, and fit. Most ballet movements are composed of jumping, balancing, landing, and spinning. Wearing 5-toed forefoot shoes allows for a natural range of movement in each toe, to improve both tecltnique and balance. Pain and injuries from ballet can be minimized by wearing the correct shoe type. According to this analysis, it is possible to customized ballet shoes to increase the efficiency of techniques and movements. Keywords : Ground Reaction Force, Qualitative Elements, Grand Jete, 5-Toed Forefoot Shoes